The pitfall of the transient, inconsistent anticancer capacity of antiestrogens and the mechanism of apparent antiestrogen resistance - Suba Z (Dove Medical Press, 2015)
Zsuzsanna Suba National Institute of Oncology, Surgical and Molecular Tumor Pathology Centre, Budapest, Hungary Abstract: Although antiestrogens have been available for breast cancer therapy since the early 1970s, neither their inconsistent anticancer capacity nor the developing antiestrogen resistance of tumors can be fully understood. Although clinical and experimental investigations revealed many tiny details concerning the link between estrogen signaling and tumor development, they yielded fairly controversial findings. Estrogen receptor (ER) overexpression in tumor cells induced by estrogen treatment was erroneously regarded as a promoter of DNA damage, genomic instability, and tumor growth. Similarly, compensatory ER overexpression caused by antiestrogen treatment or estrogen withdrawal was mistakenly evaluated as a key for rapid tumor growth attributed to acquired antiestrogen resistance. Nevertheless, ER upregulation induced by estrogen treatment is a physiologic process even in tumor cells, whereas in the case of antiestrogen administration, it is a contraregulatory action to defend the endangered estrogen signaling. Upregulation of estrogen signaling displays a unique dichotomy, ensuring the survival and safe proliferative activity of healthy cells, while inducing apoptotic death of malignant tumor cells. Analysis of the fairly controversial results justifies that whatever type of available endocrine therapies may be used, including estrogen, antiestrogen treatment, or oophorectomy, an extreme upregulation of ER signaling seems to be the crucial mechanism of successful prevention and treatment for breast cancer. The inconsistent therapeutic effects of antiestrogen administration may be explained by the different genetic capacities of patients for the compensatory upregulation of ER and aromatase enzyme expressions. The weaker the defensive counteraction against the inhibition of estrogen signaling, the poorer is the prognosis of the disease. De novo or acquired antiestrogen resistance of tumors may be associated with the missing capacity of patients for the extreme upregulation of estrogen signaling or with the exhaustion of defensive counteractions in cases that previously showed good reactivity. High-dose estrogen treatment is capable of restoring ER signaling and anticancer capacity even after heavy exposure to antiestrogen therapy. Keywords: estrogen, estrogen signaling, estrogen receptor, breast cancer, BRCA gene mutation, estrogen hypersensitivity